Scroll:Algebra >> subtract >> ps (4185)


Written Instructions:

For each Multiple Choice Question (MCQ), four options are given. One of them is the correct answer. Make your choice (1,2,3 or 4). Write your answers in the brackets provided..

For each Short Answer Question(SAQ) and Long Answer Question(LAQ), write your answers in the blanks provided.

Leave your answers in the simplest form or correct to two decimal places.



 

1)  

 Solve the following.

subtract 4ab + 6bc - 11ac from 16ab - 11bc + 9ca


___ca


Answer:_______________




2)  

 Solve the following.

subtract 7ab + 13bc - 20ac from 21ab - 18bc + 7ca


___ca


Answer:_______________




3)  

 Solve the following.

subtract 8ab + 11bc - 7ac from 19ab - 13bc + 17ca


___ca


Answer:_______________




4)  

 Solve the following.

subtract 6ab + 19bc - 13ac from 13ab - 18bc + 18ca


___ca


Answer:_______________




5)  

 Solve the following.

subtract 9ab + 15bc - 11ac from 14ab - 8bc + 14ca


___ca


Answer:_______________




6)  

 Solve the following.

subtract 2ab + 8bc - 10ac from 16ab - 13bc + 5ca


___ca


Answer:_______________




7)  

 Solve the following.

subtract 2ab + 14bc - 4ac from 14ab - 14bc + 17ca


___ca


Answer:_______________




8)  

 Solve the following.

subtract 2ab + 7bc - 3ac from 13ab - 16bc + 15ca


___ca


Answer:_______________




9)  

 Solve the following.

subtract 6ab + 14bc - 11ac from 13ab - 6bc + 3ca


___ca


Answer:_______________




10)  

 Solve the following.

subtract 9ab + 6bc - 20ac from 21ab - 15bc + 9ca


___ca


Answer:_______________




 

1)  

 Solve the following.

subtract 4ab + 6bc - 11ac from 16ab - 11bc + 9ca


Answer: 12ab 

Answer: -17bc

Answer: 20ca


SOLUTION 1 :

 (16ab - 11bc + 9ca) - (4ab + 6bc - 11ca)

= 16ab - 11bc + 9ca - 4ab - 6bc + 11ca
= (16ab - 4ab) + (-11bc - 6bc) + (9ca + 11ca)
= (16 - 4)ab + (-11 - 6)bc + (9 + 11)ca
= 12ab  -17bc + 20ca


2)  

 Solve the following.

subtract 7ab + 13bc - 20ac from 21ab - 18bc + 7ca


Answer: 14ab 

Answer: -31bc

Answer: 27ca


SOLUTION 1 :

 (21ab - 18bc + 7ca) - (7ab + 13bc - 20ca)

= 21ab - 18bc + 7ca - 7ab - 13bc + 20ca
= (21ab - 7ab) + (-18bc - 13bc) + (7ca + 20ca)
= (21 - 7)ab + (-18 - 13)bc + (7 + 20)ca
= 14ab  -31bc + 27ca


3)  

 Solve the following.

subtract 8ab + 11bc - 7ac from 19ab - 13bc + 17ca


Answer: 11ab 

Answer: -24bc

Answer: 24ca


SOLUTION 1 :

 (19ab - 13bc + 17ca) - (8ab + 11bc - 7ca)

= 19ab - 13bc + 17ca - 8ab - 11bc + 7ca
= (19ab - 8ab) + (-13bc - 11bc) + (17ca + 7ca)
= (19 - 8)ab + (-13 - 11)bc + (17 + 7)ca
= 11ab  -24bc + 24ca


4)  

 Solve the following.

subtract 6ab + 19bc - 13ac from 13ab - 18bc + 18ca


Answer: 7ab 

Answer: -37bc

Answer: 31ca


SOLUTION 1 :

 (13ab - 18bc + 18ca) - (6ab + 19bc - 13ca)

= 13ab - 18bc + 18ca - 6ab - 19bc + 13ca
= (13ab - 6ab) + (-18bc - 19bc) + (18ca + 13ca)
= (13 - 6)ab + (-18 - 19)bc + (18 + 13)ca
= 7ab  -37bc + 31ca


5)  

 Solve the following.

subtract 9ab + 15bc - 11ac from 14ab - 8bc + 14ca


Answer: 5ab 

Answer: -23bc

Answer: 25ca


SOLUTION 1 :

 (14ab - 8bc + 14ca) - (9ab + 15bc - 11ca)

= 14ab - 8bc + 14ca - 9ab - 15bc + 11ca
= (14ab - 9ab) + (-8bc - 15bc) + (14ca + 11ca)
= (14 - 9)ab + (-8 - 15)bc + (14 + 11)ca
= 5ab  -23bc + 25ca


6)  

 Solve the following.

subtract 2ab + 8bc - 10ac from 16ab - 13bc + 5ca


Answer: 14ab 

Answer: -21bc

Answer: 15ca


SOLUTION 1 :

 (16ab - 13bc + 5ca) - (2ab + 8bc - 10ca)

= 16ab - 13bc + 5ca - 2ab - 8bc + 10ca
= (16ab - 2ab) + (-13bc - 8bc) + (5ca + 10ca)
= (16 - 2)ab + (-13 - 8)bc + (5 + 10)ca
= 14ab  -21bc + 15ca


7)  

 Solve the following.

subtract 2ab + 14bc - 4ac from 14ab - 14bc + 17ca


Answer: 12ab 

Answer: -28bc

Answer: 21ca


SOLUTION 1 :

 (14ab - 14bc + 17ca) - (2ab + 14bc - 4ca)

= 14ab - 14bc + 17ca - 2ab - 14bc + 4ca
= (14ab - 2ab) + (-14bc - 14bc) + (17ca + 4ca)
= (14 - 2)ab + (-14 - 14)bc + (17 + 4)ca
= 12ab  -28bc + 21ca


8)  

 Solve the following.

subtract 2ab + 7bc - 3ac from 13ab - 16bc + 15ca


Answer: 11ab 

Answer: -23bc

Answer: 18ca


SOLUTION 1 :

 (13ab - 16bc + 15ca) - (2ab + 7bc - 3ca)

= 13ab - 16bc + 15ca - 2ab - 7bc + 3ca
= (13ab - 2ab) + (-16bc - 7bc) + (15ca + 3ca)
= (13 - 2)ab + (-16 - 7)bc + (15 + 3)ca
= 11ab  -23bc + 18ca


9)  

 Solve the following.

subtract 6ab + 14bc - 11ac from 13ab - 6bc + 3ca


Answer: 7ab 

Answer: -20bc

Answer: 14ca


SOLUTION 1 :

 (13ab - 6bc + 3ca) - (6ab + 14bc - 11ca)

= 13ab - 6bc + 3ca - 6ab - 14bc + 11ca
= (13ab - 6ab) + (-6bc - 14bc) + (3ca + 11ca)
= (13 - 6)ab + (-6 - 14)bc + (3 + 11)ca
= 7ab  -20bc + 14ca


10)  

 Solve the following.

subtract 9ab + 6bc - 20ac from 21ab - 15bc + 9ca


Answer: 12ab 

Answer: -21bc

Answer: 29ca


SOLUTION 1 :

 (21ab - 15bc + 9ca) - (9ab + 6bc - 20ca)

= 21ab - 15bc + 9ca - 9ab - 6bc + 20ca
= (21ab - 9ab) + (-15bc - 6bc) + (9ca + 20ca)
= (21 - 9)ab + (-15 - 6)bc + (9 + 20)ca
= 12ab  -21bc + 29ca